Application of the human estrogen receptor within a synthetic transcription factor in Trichoderma reesei - Derntl, Christian (Fungal Biol Biotechnol, 2020)
BACKGROUND: Synthetic gene expression systems offer a possibility for controllable and targeted induction of the expression of genes of interest, which is a fundamental technique necessary for basic research and industrial applications. The human estrogen receptor α contains a ligand binding domain that enforces dimerization and nuclear import upon binding of the inducer 17β-estradiol. In this study, we tested the potential of this ligand binding domain to be used in filamentous fungi as an auto-regulatory domain in a synthetic transcription factor. RESULTS: We constructed the synthetic transcription factor SynX by fusing the DNA-binding domain of Xyr1 (Xylanase Regulator 1), the transactivation domain of Ypr1 (Yellow Pigment Regulator 1), and the ligand binding domain of the human estrogen receptor α. SynX is able to strongly induce the gene expression of xylanases and an aldose reductase by addition of 17β-estradiol, but SynX does not induce gene expression of cellulases. Importantly, the induction of xylanase activities is mostly carbon source independent and can be fine-tuned by controlling the concentration of 17β-estradiol. CONCLUSION: The ability of SynX to induce gene expression of xylanase encoding genes by addition of 17β-estradiol demonstrates that the ligand binding domain of the human estrogen receptor α works in filamentous fungi, and that it can be combined with a transactivation domain other than the commonly used transactivation domain of herpes simplex virion protein VP16.